3‐Chlorotyramine Acting as Ligand of the D2 Dopamine Receptor. Molecular Modeling, Synthesis and D2 Receptor Affinity. Issue 1 (27th November 2014) - Angelina, Emilio; Andujar, Sebastian; Moreno, Laura; Garibotto, Francisco; Párraga, Javier; Peruchena, Nelida; Cabedo, Nuria; Villecco, Margarita; Cortes, Diego; Enriz, Ricardo D.
Abstract We synthesized and tested 3‐chlorotyramine as a ligand of the D2 dopamine receptor. This compound displayed a similar affinity by this receptor to that previously reported for dopamine. In order to understand further the experimental results we performed a molecular modeling study of 3‐chlorotyramine and structurally related compounds. By combining molecular dynamics simulations with semiempirical (PM6), ab initio and density functional theory calculations, a simple and generally applicable procedure to evaluate the binding energies of these ligands interacting with the D2 dopamine receptors is reported here. These results provided a clear picture of the binding interactions of these compounds from both structural and energetic view points. A reduced model for the binding pocket was used. This approach allowed us to perform more accurate quantum mechanical calculations as well as to obtain a detailed electronic analysis using the Quantum Theory of Atoms in Molecules (QTAIM) technique. Molecular aspects of the binding interactions between ligands and the D2 dopamine receptor are discussed in detail. A good correlation between the relative binding energies obtained from theoretical calculations and experimental IC50 values was obtained. These results allowed us to predict that 3‐chlorotyramine possesses a significant affinity by the D2‐DR. Our theoretical predictions were experimentally corroborated when we synthesized and tested 3‐chlorotyramine which displayed a similar affinity by the D2‐DR to that reported for DA.